Novel KIF11 Mutation Associated with Microcephaly, Chorioretinopathy and Impaired Intellectual Development: 20 Years of Follow-Up - Ashley H. Yaskanich; Ami Patel; Monique Leys (Children)
Background: KIF11 mutations are responsible for a large portion of microcephaly with or without chorioretinopathy, lymphedema or impaired intellectual development (MCLMR). Methods: This report describes longitudinal ophthalmological management of an 8-year-old male pediatric patient presenting with MCLMR diagnosed in infancy and associated with a novel, de novo KIF11 mutation. Results: The patient presented with ophthalmological features of low visual acuity and chorioretinal atrophy and later developed bilateral retinal detachments. Syndromic features included microcephaly and developmental delay. Scleral buckling and vitrectomy were ultimately performed in both eyes, with a period of conservative management in the interim. Postoperative visual acuity was preserved in the right eye, although poor in the left eye. The patient received low-vision rehabilitation services and was able to participate in school and extracurricular activities. Conclusions: Early recognition and close monitoring of ocular and systemic manifestations of KIF11 mutations are important to optimize visual rehabilitation efforts.